2016
DOI: 10.1371/journal.pone.0162317
|View full text |Cite
|
Sign up to set email alerts
|

LBD1 of Vitellogenin Receptor Specifically Binds to the Female-Specific Storage Protein SP1 via LBR1 and LBR3

Abstract: Storage proteins are the major protein synthesized in the fat body, released into hemolymph and re-sequestered into the fat body before pupation in most insect species. Storage proteins are important amino acid and nutrition resources during the non-feeding pupal period and play essential roles for the metamorphosis and oogenesis of insects. The sequestration of storage protein is a selective, specific receptor-mediated process. However, to date, the potential receptor mediating the sequestration of storage pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
(64 reference statements)
1
13
0
Order By: Relevance
“…The presence of the 25K and 21K proteins is sex-linked and they are present only in the adult females. Initial appearance of 25K mRNA is closely coordinated in time with that of Vgs, 21K and 19K, all of which are induced by JH implying possible involvement of JH in the regulation of synthesis of the 25K protein [17]. Interesting finding of the present study is that the similar type of protein is also found in the female adult of T. castaneum which reached a maximum level over days 10-15 after the insect molted into adult.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The presence of the 25K and 21K proteins is sex-linked and they are present only in the adult females. Initial appearance of 25K mRNA is closely coordinated in time with that of Vgs, 21K and 19K, all of which are induced by JH implying possible involvement of JH in the regulation of synthesis of the 25K protein [17]. Interesting finding of the present study is that the similar type of protein is also found in the female adult of T. castaneum which reached a maximum level over days 10-15 after the insect molted into adult.…”
Section: Discussionsupporting
confidence: 64%
“…It is a dynamic tissue involved in multiple metabolic functions. The uptake of these proteins by the fat body tissue is stage specific process occurs before pupation by a receptor mediated endocytotic process [17]. One of these functions is to store and release energy in response to the energy demands of the insect.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have attempted to identify or characterize the BmSP1 receptor. A recent study showed that LBD1 of BmVgR can specifically bind to the BmSP1 (Liu et al 2016).…”
Section: R a F Tmentioning
confidence: 99%
“…BmSP1 was purified as described previously (Liu et al 2016). BmVg was purified using a method similar to that used for BmSP1.…”
Section: Purification and Fluorescent Labeling Of Bmvg And Bmsp1mentioning
confidence: 99%
“…Usually synthesized in the fat body of larvae, storage proteins are released into the haemolymph. During pupation, they are selectively reabsorbed by the fat body, where they form dense protein particles in the cell (Liu et al, 2016). Storage proteins play important physiological and biochemical roles in insects.…”
Section: Introductionmentioning
confidence: 99%